INFLUENCE OF TRAINING ON EMPLOYEE PERFORMANCE IS MODERATE BY COMPENSATION IN MILLENIAL GENERATION EMPLOYEES IN BEKASI DISTRICT - Hardianti, Yuni; Gunawan, Ahmad (LPPM STIE Muhammadiah Bandung, 2024)
This research was conducted to determine the effect of training on performance which is moderated by compensation for millennial generation employees in Bekasi Regency. This research uses a quantitative method using SPSS Version 26 and MacroProcess version 4.3 with the Hayes 1 model for the analysis method. The population in this research is millennial generation employees who work and live in Bekasi Regency with a total sample of 96 samples. The analysis results show that training has a significant effect on employee performance and compensation as a moderating variable so that compensation significantly moderates the effect of training on employee performance.